Initial Severe Acute Respiratory Syndrome Coronavirus 2 Viral Load Is Associated With Disease Severity: A Retrospective Cohort Study. (1st May 2022) - Souverein, Dennis; van Stralen, Karlijn; van Lelyveld, Steven; van Gemeren, Claudia; Haverkort, Milly; Snijders, Dominic; Soetekouw, Robin; Kapteijns, Erik; de Jong, Evelien; Hermanides, Gonneke; Aronson, Sem; Herpers, Bjorn; et al.
Abstract: Background: We assessed the association between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral load and hospital admission, intensive care unit (ICU) admission, and in-hospital mortality. Methods: All SARS-CoV-2–positive persons with a combined nasopharyngeal and oropharyngeal swab that was collected between 17 March 2020 and 31 March 2021 in public health testing facilities were included. Results: From 20 207 SARS-CoV-2–positive persons, 310 (1.5%) were hospitalized within 30 days. High viral loads (crossing point [Cp] <25) were associated with an increased risk of hospitalization as compared to low viral loads (Cp >30), adjusted for age and sex (adjusted odds ratio [aOR], 1.57 [95% confidence interval CI, 1.11–2.26]). The same association was seen for ICU admission (aOR, 7.06 [95% CI, 2.15–43.57]). The median [interquartile range] Cp value of the 17 patients who died in hospital was significantly lower compared to the 226 survivors (22.7 [3.4] vs 25.0 [5.2]). Conclusions: Higher initial SARS-CoV-2 viral load is associated with an increased risk of hospital admission, ICU admission, and in-hospital mortality. Our findings emphasize the added value of reporting SARS-CoV-2 viral load or cycle threshold/Cp values to identify persons who are at the highest risk of adverse outcomes such as hospital or ICU admission and who therefore may benefit from more intensive monitoring or early initiation of antiviral therapy. Abstract : Higher initial SARS-CoV-2 viral load is associated with an increased risk of hospital admission, intensive care unit admission, and in-hospital mortality.